First isolation report of Arcobacter cryaerophilus from a human diarrhea sample in Costa Rica - Barboza Arrieta, Karol (2017)
Arcobacter cryaerophilus is an emerging enteropathogen and potential zoonotic agent transmitted by food and water. In Costa Rica, this bacterium has not been associated with cases of human gastroenteritis, even though it has been isolated from farm animals, especially poultry. This paper reports the first isolation of A. cryaerophilus from a human case of bloody watery diarrhea and the virulence genes associated with this isolate.